Treatment of a duodenal perforation after mucosectomy: case report and literature review - Simões, João; Melo, Catarina; Camacho, Cristina; Fraga, Emília; Bernardes, António (International Surgery Journal, 2021)
Duodenal neuroendocrine tumors are rare. Its incidence is increasing due to access to upper gastrointestinal endoscopy. In early stages, endoscopic submucosal dissection is a valid approach. However, endoscopic procedures of duodenum have high risk of complications due to its particularly anatomic configuration. Perforation of duodenum is a complication from endoscopic submucosal dissection, and it is a diagnostic challenge. Abdominal computed tomography with oral contrast is the best exam to diagnose duodenum perforation. Late perforation can present with fever and tachycardia, without abdominal pain or tenderness. There is not an optimal or standard management of duodenal perforation. Medical treatment, endoscopic procedures, percutaneous drainage, or surgical approaches can be possible and valid. The patient state, anatomy and localization of perforation and surgeon experience need to be factors to have in count. The authors present a case of a large duodenal perforation after endoscopic submucosal dissection with subhepatic abscess, managed with surgical approach, performing an antrectomy with Y-en-Roux gastrojejunostomy and duodenostomy with a Pezzer tube. The patient started oral feeding on fifth day post-operative, and performed a fistulography on twentieth day post-operative, without contrast leak. Discharged occurred on post-operative day 41 without main complications. The Pezzer tube was removed four months after surgery, and one month later the abdominal wound where Pezzer tube was, closed.